Essential leadership skills for project managers in Malaysia - Ang, Li Kai (2022)
A project manager is an individual that is appointed by the performin organization to manage the entire project team that works towards the same g direction to achieve the project’s goals and objectives (Anantatmula, 2010). Therefore, it is very important for a project manager to equip himself with a lot of skills to become a successful and competent project manager. Despite the importance of the key industry sector such as the manufacturing sector, services sector, construction sector, agriculture sector, and hospitality sector to Malaysia’s economic development, there are s till many project management problems exist within all these sectors (Tabassi et al., 2019). The lack of competent project managers is one of the main factors that lead to all of these project management problems (Zimmerer and Yasin. 1998). Thus, a total o f ten (10) main differences between management skills and leadership skills were identified through comprehensive literature review. Not only that, but there are also nine (9) leadership skills required for project managers and five (5) strategies to impro ve leadership skills for project managers were identified through comprehensive literature review. This paper adopted quantitative research approach which all the data were obtained from 138 project managers from several industry sectors within Klang Valle y region through questionnaire. The data collected was then evaluated by statistical method using Microsoft Office Excel and Statistical Package for the Social Science (SPSS) where appropriate to produce a ranking of all variables. The results of analysis indicate that the code “B.04” or “ Leader often will advocate change and suggest innovative ideas throughout the project while managers promote stability to get their project done” has the highest level of agreement as the main differences between manageria l skills and leadership skills among the respondents. Meanwhile, the result also revealed that the “C.03” or “Decisionmaking skill” is the most important skill that a competent project manager should possess. Last but not least, this study empirically dem onstrates that code “D.05” or “Extrinsic Reward” is the most effective strategy to improve leadership skills for project managers. In a nutshell, this study has resulted in a useful list of main differences between managerial skills and leadership skills t hat is relevant to the Malaysian industry sector. Not only that, the list of strategies to improve leadership skills for project managers can also be utilised as reference points for the employers in Malaysian industry sector to improve project managers’ l eadership skills in the future.